The Perceptions of Small Businesses in the Implementation of Cash Management Techniques - Mungal, Avika (Journal of Economics and Behavioral Studies, 2014)
The purpose of this paper is to ascertain the perceptions of small business owners on the implementation of cash management techniques in their businesses. This paper also highlights the importance of managing cash inflow and outflow in the business and examines the impact on business profitability and sustainability. The study focused on small businesses in the Tongaat area, South Africa. This research was quantitative, descriptive and cross-sectional in nature. The instrument used to extract the relevant data from respondents was a Likert type questionnaire. The findings of this research identified the perceptions of small business cash management techniques. A short course on cash management could be offered by the Durban University of Technology to small business owners and managers to enhance their basic cash management knowledge in the implementation of cash management techniques.